Predicting pathological jaundice in term babies with ABO setting using cord blood bilirubin - Panneerselvam, Karthikeyan; Mani, Sathyamoorthy; Ramraj, Balaji; Pasupathy, Sekar; Munusamy, Muthulakshmi; Sundar, Subash (Indian Journal of Child Health, 2018)
Background: Cord blood bilirubin analysis helps not only in predicting the pathological jaundice in ABO incompatibility but is also useful for early referral and intervention for better outcome. Objective: The objective of this study was to identify the best cut off value of cord blood bilirubin for predicting pathological hyperbilirubinemia in newborns with ABO setting. Materials and Methods: This cohort study was conducted in the Department of Pediatrics at a Medical College during February 2018–July 2018. In this study, healthy term babies with blood Group A, B, and AB born to O positive mothers with birth weight >2.5 kgs and gestational age >37 weeks were included in the study. Cord blood bilirubin and the 4th day (>72 h of life) serum bilirubin value were evaluated. Receiver operating characteristic curve and sensitivity and specificity were used to analyze the data. Results: A total of 70 babies were studied; of which, 45 babies developed physiological jaundice and 25 developed pathological jaundice. The mean cord blood bilirubin value of newborns with physiological jaundice was 2.2 mg/dl, while the value among pathological jaundice was 2.6 mg/dl. Taking cord blood bilirubin value of 2.25 mg/dl as cutoff, the sensitivity and specificity of predicting pathological jaundice was 84% and 71.1%, respectively. Conclusion: Babies with cord bilirubin >2.25 mg/dl are more prone to pathological hyperbilirubinemia.